Auditoría interna de propiedad planta y equipos y la razonabilidad en los estados financieros en las empresas privadas del sector salud - Quinteros Chiliquinga, Ana Dolores (2021)
The present research work entitled "INTERNAL AUDIT OF PLANT PROPERTY AND EQUIPMENT AND THE REASONABILITY OF THE FINANCIAL STATEMENTS IN PRIVATE COMPANIES IN THE HEALTH SECTOR", was carried out with the purpose of obtaining information on the processes of Internal Control established in the companies of the Health sector to safeguard its Property, Plant and Equipment and its effect on the fair presentation in the financial statements. The justification for this research is because Property, Plant and Equipment are essential for the development of operational activities in companies that provide health services; Due to the items they include such as medical and scientific equipment and physical structures, they are a large investment and these assets are the basis for performing the medical services provided by these entities............